Analysis of Virtual Communication Patterns in Online Gaming Communities (Case Study: Game Podcasts in the Roblox Application) - Negara, Ibanez Citra; Siswoyo, Mukarto; Hermawan, Abdul Jalil (Indonesian Journal of Advanced Research, 2026)
This study examines virtual communication patterns in online gaming communities, with the case study focusing on podcast games within the Roblox application, specifically the Chaos Crew Podcast community. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving hosts or moderators, players, and listeners. The analysis was guided by Computer Mediated Communication (Walther 1996) and Virtual Community (Howard Rheingold). The findings show that virtual communication in this community takes three main forms: synchronous communication via voice chat, asynchronous communication via text chat, and symbolic communication via avatar expressions. Member interactions develop gradually from the introductory stage to more personal relationships, supported by factors such as identity anonymity.